FEEDING ECOLOGY OF TREE-CLIMBING MANGROVE SESARMID CRABS FROM LUZON, PHILIPPINES - JIMMY TEVAR MASAGCA (SEAMEO BIOTROP, 2009)
Despite the large ecological study of tree-climbing mangrove sesarmid crabs in other countries, the Philippine representatives appear to have not been investigated extensively. This paper presents the feeding ecology as to dependence on mangrove trees of sesarmids in different mangrove areas of southern Luzon. This is biased on the nature of the crab habitats, arboreal climbing skills and burrowing behavior of the sesarmids: Selatium elongatum and Episesarma versicolor - exclusive mangrove tree climbers (EMTC); Sarmatium germaini - occasional mangrove tree climber (OMTC); and the non-mangrove tree-climbing (NMTC) sesarmids- Neosarmatium smithii, Perisesarma bidens and Perisesarma eumolpe.Key words: mangrove crabs, sesarmid crabs, climbing skills, burrowing skills, arboreal climbing crabs, Catanduanes, Philippines